2016
DOI: 10.1002/etc.3636
|View full text |Cite
|
Sign up to set email alerts
|

Response and recovery of the macrophytes Elodea canadensis and Myriophyllum spicatum following a pulse exposure to the herbicide iofensulfuron‐sodium in outdoor stream mesocosms

Abstract: Interest in stream mesocosms has recently revived for higher tier aquatic macrophyte risk assessment of plant protection products mainly because 1) the highest predicted environmental concentrations for the assessment of effects are frequently derived from stream scenarios, and 2) they allow an effect assessment using stream-typical pulse exposures. Therefore, the present stream mesocosm study used an herbicide pulse exposure and evaluated the responses of Elodea canadensis and Myriophyllum spicatum. Macrophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…If we consider the endpoint TSL, we observed a maximum growth rate of 0.072 day −1 . This is higher than those reported from laboratory single species tests (0.050 ± 0.014 day −1 ; Knauer et al, 2006) and from a mesocosm study (0.039 ± 0.006 day −1 ; Knauer et al, 2008), and lies in the same range as that reported by Wieczorek et al (2017), who found a maximum growth rate of 0.078 ± 0.007 day −1 . The lower values reported by Knauer et al (2006) refer to a water-only M. spicatum study lacking any sediment.…”
Section: Growth Rates Of M Spicatum Under Outdoor Conditionscontrasting
confidence: 56%
See 1 more Smart Citation
“…If we consider the endpoint TSL, we observed a maximum growth rate of 0.072 day −1 . This is higher than those reported from laboratory single species tests (0.050 ± 0.014 day −1 ; Knauer et al, 2006) and from a mesocosm study (0.039 ± 0.006 day −1 ; Knauer et al, 2008), and lies in the same range as that reported by Wieczorek et al (2017), who found a maximum growth rate of 0.078 ± 0.007 day −1 . The lower values reported by Knauer et al (2006) refer to a water-only M. spicatum study lacking any sediment.…”
Section: Growth Rates Of M Spicatum Under Outdoor Conditionscontrasting
confidence: 56%
“…The maximum biomass‐based growth rates of M. spicatum shoots found in our study in the first summer (0.085 day −1 for DW biomass; see Supporting Information S1) were of the same order of magnitude or higher than those found in 21‐day single species laboratory test that included a sediment in the test design (0.056 ± 0.007 day −1 for biomass; Knauer et al, 2006), as well as in biomass‐based tests reported in a 20‐day outdoor mesocosm study (0.068 ± 0.014 day −1 ; Knauer et al, 2008), and in a stream mesocosm study (Wieczorek et al, 2017; maximum mean growth rate for total shoot DW 0.066 ± 0.010 day −1 ). If we consider the endpoint TSL, we observed a maximum growth rate of 0.072 day −1 .…”
Section: Discussionmentioning
confidence: 77%
“…Finally, it is useful in setting regulatory requirements by demonstrating the size effect that can be reasonably required in an estimate. MDD% has been applied to a class of ecological studies by Brock et al (2015) and Wieczorek et al (2017) and used in EFSA guidance (EFSA 2013), USEPA publications (e.g., Harcum and Dressing 2015), and in clinical trials (Meinert 2012). The concept sometimes appears under names such as minimal detectable difference or minimum detectable change.…”
Section: Analysis Approachmentioning
confidence: 99%
“…All growth endpoints have comparable sensitivity to IMS except for dry weight shoots, where no clear dose response was observed; furthermore, the estimates were unreliable because of the negative confidence intervals derived (Table 2). Several studies have also reported no effects on dry weight shoots of aquatic plants when exposed to sulfonylurea herbicide (Nuttens et al, 2016; Wendt‐Rasch et al, 2003; Wieczorek et al, 2017).…”
Section: Discussionmentioning
confidence: 99%